Maestri viennesi Haydn, Mozart, Beethoven, Schubert ; verso e oltre - Piccardi, Carlo 1942- (Ricordi [u.a.], 2011)
Literaturverz. S. [700] - 727
Includes bibliographical references (p. [700]-727) and index
Keywords: Geschichte 1700-1800; Klassik; Wiener Klassik; Musik